Design of single‐span beams for SLS and ULS using semi‐continuous beam‐to‐column joints: Part 2: Composite beams with variable bending stiffness and joints according to EN 1993‐1‐8. Issue 2 (May 2017) - da Costa, Job Duarte; Obiala, Renata; Odenbreit, Christoph; Braun, Matthias
Abstract: The objective of this article is to facilitate the use of semi‐continuous joints by providing ready‐to‐use tables and charts for design, which also permit the benefits accruing from the use of semi‐continuous composite beams to be directly identified. The relevant features for the design of composite beams, such as bending moment distribution, maximum deflection and natural frequency, are derived analytically. The influence of semi‐continuous steel joints on the performance of single‐span composite beams is analysed. The article concludes with an example of the use of a new slim‐floor beam type – the composite slim‐floor beam (CoSFB). The tables and charts derived are applied in this example with the intention of demonstrating the advantages of using semi‐continuous joints in combination with composite beams. The present article extends the design of semi‐continuous steel beams presented in the previous article on this subject [1].